Some cultural strategies for management of bean stem maggots (Diptera: Agromyzidae) on beans in Tanzania - Ampofo, James Kwasi O.; Massomo, S.M.S. (1998)
We compared cultural practices commonly used in bean (Phaseolus vulgaris L.) and other vegetable cropping systems to assess the effect of individual as well as combinations of practices on bean stem maggot (BSM) (Ophiomyia spp. Diptera: Agromyzidae) infestation and subsequent damage to bean plants. The cultural practices used included mulching, application of fertilizer and chemical seed dressing. Chemical seed dressing reduced pest incidence during early growth stages and enhanced plant survival. Mulches and application of fertilizer did not reduce pest infestation but enhanced plant tolerance to the pest; it also reduced subsequent plant mortality compared to the control. Combinations of these practices were even more effective in reducing BSM induced plant mortality and increasing crop yield. Their efficiencies varied with location.